Digital storytelling: an integrated approach to language for the 21st century student - Ribeiro, Sandra (2015)
Societal changes have, throughout history, pushed the long-established boundaries of education across all grade levels. Technology and media merge with education in a continuous complex social process with human consequences and effects. We, teachers, can aspire to understand and interpret this volatile context that is being redesigned at the same time society itself is being reshaped as a result of the technological evolution. The language- learning classroom is not impenetrable to these transformations. Rather, it can perhaps be seen as a playground where teachers and students gather to combine the past and the present in an integrated approach. We draw on the results from a previous study and argue that Digital Storytelling as a Process is capable of aggregating and fostering positive student development in general, as well as enhancing interpersonal relationships and self-knowledge while improving digital literacy. Additionally, we establish a link between the four basic language-learning skills and the Digital Storytelling process and demonstrate how these converge into what can be labeled as an integrated language learning approach.